NELAYAN DESA BENDAR: STRATEGI DALAM MENGATASI KENDALA USAHA PERIKANAN TANGKAP - Manan, M. Azzam (Jurnal Masyarakat dan Budaya, 2015)
This article is a part of research findings on fishermen, conducted in 2009 at fishing village of Bendar in Pati Region of Central Java Province. The study shows that fishermen basically face a number of handicaps or problems, concerning with regulations that forbid operating cantrang nets and sale of fish over the sea, bureaucracy difficulties in terms of officials’ negative mental attitude, lack of capital, market system based on middle man, and instability in income generation. As a means of production, cantrang nets are extremely prohibited to operate due to considered similar to trawl nets in the way of operation. The study is basically a qualitative research in which informants and key persons come from fishermen themselves and informal leaders in local community. A number of questions as listed in interview guide have been addressed to all of them and designed to get information in-depth as primary data. In addition, the study also collects some data from other sources as secondary data to support primary data. In coping with such problems, some actions have been done both by fishermen and government. Regarding to regulations on cantrang nets operation, Fishery and Marine of Central Java Office enforces a special policy that allows such gear to operate only by vessels with 29 GT or below in size. However, in sight of fishermen this policy is not a real or an expected solution. Therefore, as a preferred kind of gear they want all cantrang nets in any size are allowed to operate without any limitation. In connecting with other barriers, fishermen get loans from local banks to overcome the lack of capital, bridge good communication with middle men, and offer profit sharing system to the crews.